Critical theology against US militarism in Asia decolonization and deimperialization - Kim, Nami; Joh, Wonhee Anne (New approaches to religion and power, 2016)
The book investigates the ways in which Christianity (broadly defined), in its own complexity, has been complicit in maintaining and reinforcing US imperialist military agendas in both national and international contexts. Conversely, the volume also discusses the various sites and instances where Christianity has managed to serve as a force of resistance against US imperialist militarism.